The Clinicopathological Risk Factors in Renal Cell Cancer for the Oncological Outcomes Following Nephron-Sparing Surgery: A PRISMA Systematic Review and Meta-Analysis - Zhang, Lijin; Wu, Bin; Zha, Zhenlei; Qu, Wei; Zhao, Hu; Yuan, Jun (Frontiers in Oncology, 2020)
Background and objectives: Published data from individual studies present conflicting evidence about the relationship between clinicopathological risk factors and oncological outcomes in renal cell cancer (RCC) following nephron-sparing surgery (NSS). This study was conducted to explore the potential risk factors for RCC progress after NSS. Methods: Studies published in PubMed, Web of Science, and EMBASE were systematically reviewed from inception to March 2019 to determine risk factors for RCC following NSS. The predictive ability of identified predictors was assessed by hazard ratios (HRs) with 95% confidence intervals (CIs). A fixed-effect or random-effect was used to pool the estimates. Subgroup analyses were performed to explore the source of heterogeneity. Results: Seventeen studies including 38,522 patients with RCC were analyzed. The meta-analysis indicated that positive surgical margin (pooled HR=1.47; 95% CI:1.24–1.73; P<0.001), higher Fuhrman grade (pooled HR = 1.58; 95% CI:1.10–2.28; P = 0.013), higher pathological stage (pooled HR = 1.72; 95% CI:1.40–2.12; P<0.001) and large tumor size(pooled HR = 1.09; 95% CI:1.03–1.16; P = 0.003) were significantly associated with recurrence risk. However, age (pooled HR = 1.00; 95% CI: 1.00–1.01; P = 0.257), sex (male vs. female) (pooled HR = 1.04; 95% CI: 0.89–1.21; P = 0.605) and surgical approach (laparoscope vs. open) (pooled HR = 0.80; 95% CI: 0.59–1.07; P = 0.129) had no effect on recurrence after NSS. In addition, we found that positive surgical margin was significantly associated with recurrence-free survival (pooled HR = 1.87; 95% CI: 1.32–2.66; P<0.001) and overall mortality (pooled HR = 1.15; 95% CI: 1.07–1.23; P<0.001), as well as large tumor size for recurrence-free survival (pooled HR = 1.18; 95% CI: 1.06–1.30; P = 0.002)and overall mortality (pooled HR = 1.01; 95% CI: 1.00–1.02; P = 0.004). Conclusions: Unfavorable pathological characteristics were distinctly related to worse oncological outcomes in RCC patients following NSS. These results may contribute to proposed prediction models for RCC patients to aid in counseling and risk stratiﬁcation.